Antimicrobial effectiveness of ultra-fine ozone-rich bubble mixtures for fresh vegetables using an alternating flow. (August 2017) - Ushida, Akiomi; Koyama, Takahiro; Nakamoto, Yoshinori; Narumi, Takatsune; Sato, Taisuke; Hasegawa, Tomiichi
Abstract: The consumption of fresh vegetables has been increasing in part owing to an increase in awareness of their health benefits. Chemicals are used for washing fresh vegetables in washing fresh vegetables to remove surface micro-organisms. However, the effect of these chemicals on human health must be considered, and the chemical concentrations used should be minimal. Previous studies have examined washing fresh vegetables with electrolyzed water, fine bubbles, and ultra-fine bubbles with strong mechanical action. A technique using fine and ultra-fine bubbles containing ozone and chlorine has also been developed. Although the efficiency of these techniques for washing fresh vegetable was high, the observations of fine and ultra-fine bubbles were limited. In the present study, the effect of fine and ultra-fine bubbles on the washing rate of fresh vegetables in an alternating flow, which has a stronger mechanical action for washing, was investigated. Although all results in no mechanical action were the almost same ( ≒ 6.1 log cfu/g), the difference between the washing result (5.9 log cfu/g) for deionized water and those (5.3 log cfu/g) for ultra-fine bubble was obtained in an alternating flow. Moreover, the resultant viable bacterial count (3.7 log cfu/g) for ultra-fine ozone-rich bubble was less than that (4.6 log cfu/g) for sodium hypochlorite alone. There were substantial differences between washing with deionized water alone and with ultra-fine (ozone-rich) bubble mixtures. Stronger washing effects were obtained when ultra-fine (ozone-rich) bubble mixtures were combined with an alternating flow. Furthermore, surface tension, free radicals, mechanical action, and limitation of the effect was discussed for understanding the experimental results. Highlights: Washing effect of ultra-fine ozone-rich bubble mixtures was investigated in an alternating flow. Fresh Chinese cabbage was washed, and the viable bacterial count was observed. To discuss the experimental results, static and dynamic surface tensions were measured. Effect of the mechanical action and the limitation of the effect was discussed.